Dissemination of microorganisms through the coat of health professionals: an integrative review (Research, Society and Development, 2020)
Objective: To analyze the published scientific literature regarding the microbiological contamination of the coat of health professionals. Methodology: This is an integrative review of the literature in which searches for scientific materials were carried out in the databases of PubMed, Science Direct, Scientific Eletronic Library Online (SciELO) and Virtual Health Library (VHL), published between the years of 2010 and 2020. In total, 174 documents were found, of which 29 were analyzed in full and 14 included in this study. Results and Discussion: The analysis showed the contamination of lab coats by several bacterial species, with emphasis on Staphylococcus spp., In addition to a single study having detected species of fungi of the genus Candida sp. As for the sensitivity profile, recovery of vancomycin and ampicillin-resistant Staphylococcus aureus was observed, followed by other species resistant to Cotrimaxozol. Related to the level of evidence of the studies analyzed, most express a certain limitation, without strong evidence in the face of clinical applications. Final Considerations: New studies are suggested that express stronger levels of evidence, highlighting the implementation of measures that emphasize greater care with lab coats, awareness of their private use in their own environments and aspects involved in resistance, in the cross-transmission of microorganisms and in the development of Health Care-Related Infections (HCRI).